In Vivo Imaging of Transplanted Pancreatic Islets - Kim, Donghee; Jun, Hee-Sook (Frontiers in Endocrinology, 2018)
The beta-cells in the islets of Langerhans in the pancreas secrete insulin and play an important role in glucose homeostasis. Diabetes, characterized by hyperglycemia, results from an absolute or a relative deficiency of the pancreatic beta-cell mass. Islet transplantation has been considered to be a useful therapeutic approach, but it is largely unsuccessful because most of the transplanted islets are lost in the early stage of transplantation. To evaluate the efficacy of intervention methods for the improvement of islet survival, monitoring of the functional islet mass is needed. Various techniques to image and track transplanted islets have been investigated to assess islets after transplantation. In this review, recent progresses in imaging methods to visualize islets are discussed.